Identifikasi Kesulitan dan Etos Belajar Mahasiswa pada Pembelajaran Berbasis Kasus (Case Based Learning) di Program Studi Ilmu Kesehatan Masyarakat Universitas Jambi - Fitri, Adelina; Ningsih , Vinna Rahayu; Putra, Ashar Nuzulul; Putri, Fitria Eka; Hubaybah, Hubaybah (PGRI Kota Semarang, 2024)
The learning system that only focuses on delivering material from lecturers should be replaced with two-way learning between lecturers and students. Case-Based Learning (CBL) is one of the learning systems that emphasizes student activeness during lectures. The role of the lecturer is no longer as a material provider with the lecture method, but only as a facilitator in providing direction to students so that the discussion does not get out of the substance of the ongoing course. From the research, it was found that students have difficulty learning CBL if there are other activities outside of learning, such as extracurricular activities, family problems, and even romance. For their own learning ethos, students have enthusiasm if the lecture is conducted using the CBL method. They are eager to find out about the cases given, do assignments without delay, and have a high level of confidence when doing assignments. Difficulties in applying CBL in Epidemiology Methods courses come from non-academic sources, such as family problems, extracurricular activities. Lecturers as educators are expected to apply various learning methods, and involve students more actively during lectures.